2009
DOI: 10.1007/s10725-009-9372-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide counteracts chlorophyll loss in sweetpotato seedling leaves and alleviates oxidative damage against osmotic stress

Abstract: In this paper, effect of NaHS, a hydrogen sulfide (H 2 S) donor on chlorophyll and antioxidant metabolism in seedling leaves of sweetpotato under osmotic stress was investigated. With the enhancement of osmotic stress, which was mimicked by PEG-6000, chlorophyll in seedling leaves of sweetpotato (Ipomoea batatas) decreased dramatically. At 15% PEG (w/v), chlorophyll concentration reached only 50% compared with that of the controls. The osmotic-induced decrease in chlorophyll concentration could be alleviated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 40 publications
13
105
0
1
Order By: Relevance
“…In present study, pretreatment with NaHS enhanced survival percentage of 2.5-dayold maize seedlings in a concentration-dependent manner (Fig. 1), consistent with the results of Zhang et al (2009bZhang et al ( , 2010a in wheat and sweetpotato under Cr and osmotic stress. All of above-mentioned studies indicated that H 2 S may be relative to the acquisition of stress tolerance including heat tolerance in plants, but their mechanisms are not fully clear.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In present study, pretreatment with NaHS enhanced survival percentage of 2.5-dayold maize seedlings in a concentration-dependent manner (Fig. 1), consistent with the results of Zhang et al (2009bZhang et al ( , 2010a in wheat and sweetpotato under Cr and osmotic stress. All of above-mentioned studies indicated that H 2 S may be relative to the acquisition of stress tolerance including heat tolerance in plants, but their mechanisms are not fully clear.…”
Section: Discussionsupporting
confidence: 90%
“…Exposure of alfalfa (Medicago sativa) to 100 mM NaCl, seed germination and thereafter seedling growth were inhibited, but this negative effects could significantly be attenuated by NaHS at 100 µM . Zhang et al (2009b) reported that osmotic stress mimicked by PEG-6000 decreased dramatically chlorophyll in seedling leaves of sweetpotato (Ipomoea batata), and the osmotic-induced decrease in chlorophyll concentration was alleviated by spraying NaHS in a dose-dependent manner, similar to the reports of Zhang et al (2010b) in wheat seedlings. Also, In bermudagrass, exogenous application of NaHS improved salt (150 and 300 mM NaCl), osmotic (15% and 30% PEG6000) and cold (4 • C) tolerances, which were evidenced by decreased electrolyte leakage and increased survival rate under stress conditions (Shi et al 2013).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Fresh plant samples were extracted in 100 mM phosphate buffer (Zhang et al, 2009) and the supernatant was used for the APX activity and CAT activity assays (Parida and Jha, 2010). The results are presented in mmol H 2 O 2 destroyed per minute per g of fresh weight (mmol H 2 O 2 min x1 g FW x1 ).…”
Section: Growth Measurements and Chemical Analysismentioning
confidence: 99%
“…For the gel in (c), homogentes were incubated with 25 mm edtA to inactivate α-amylase and for (d), they were heated at 70°c to inactivate β-amylase. SO 2 injury, 10,20 and abiotic stresses tolerance in plants treated with H 2 S donor, 1,[21][22][23][24] all infer that H 2 S is involved in these responses.…”
mentioning
confidence: 99%